Pengaruh Self-Efficacy, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kepuasan kerja Pegawai Honorer di Kantor Kecamatan Andir Kota Bandung - Hasanah, Siti Aisyah; Muttaqin, Ridlwan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Human resources are a factor in achieving the goals and progress of a company. Employee performance greatly determines the good or bad of an organization. Therefore, management needs to pay serious attention to various aspects related to human resources, so that employees can feel satisfaction in their work, which in turn will contribute to higher performance. Employees who are satisfied with their jobs tend to be more productive and have a lower likelihood of leaving their jobs. There are several factors that influence job satisfaction, including Self-Efficacy, which increases employees' ability to carry out tasks, work discipline, a sense of obedience to regulations and an adequate work environment. This study aims to determine the effect of Self-Efficacy, Work Discipline, and Work Environment on Job Satisfaction of honorary employees at the Andir District Office, Bandung City. Data were collected using a quantitative approach through a questionnaire distributed to 30 people who were the population and sample of the study. Sample selection was carried out using the saturated sample method. Statistical analysis includes verification analysis, coefficient of determination, and hypothesis testing individually and quantitatively. This analysis was carried out using SPSS 25.